PTU-105 The cost burden of coeliac disease on a DGH endoscopy unit: a 12 year retrospective review. (8th June 2018) - Johnson, Matt W; Bhuva, Meha; Rostami, Kamran; Patel, Jay
Abstract : Introduction: Financial pressure within the NHS has recently led to many Clinical Commissioning Groups (CCG) decommissioning gluten free prescriptions. However, little is known about the direct economic impact of coeliac disease (CD) in UK, thought to affect 1 in 100 people. This includes costs related to inpatient stay and towards the endoscopy unit. In order to attract appropriate, yet fair, future funding from our local CCG for treating coeliac patients, the existing expenditure needs to be acknowledged. Endoscopy with histopathological analysis of duodenal biopsies is still the gold standard for diagnosing coeliac disease. Furthermore, both upper and lower endoscopy allows the important investigation of symptoms encountered by CD patients. The objective of this study was to assess the demand and costs of GI endoscopic procedures in relation to the management of CD, over a 12 year period. Method: The Luton and Dunstable University Hospital has a database of 1317 patients with coeliac disease. [Male n=467, Female n=850; Age range: 1–102 years old; mean age 58]. Using the database for reference, the hospital coding system was used to analyse the total number of upper and lower GI endoscopy procedures performed for these patients during 2005–2016. The total cost for the Luton CCG was then calculated based on the latest Department of Health National Tariff, awarding £375 for an OGD with biopsy; £474 for colonoscopy with biopsy; £391 for flexible sigmoidoscopy with biopsy; £914 for Video Capsule Endoscopy (VCE) and £945 for ERCP. The Luton CCG reimburses (tariff cost x 1.120265) to the hospital. Results: Over the 12 year period, the 1317 known coeliac patients underwent a total 689 OGDs (cost £258, 375), 413 colonoscopies (£195, 762), 108 flexible sigmoidoscopies (£42, 228), 6 pouchoscopies (£2, 346), 8 VCE's (£7312) and 3 ERCP's (£2835). 353 patients were newly diagnosed with coeliac disease histopathologically, costing £132, 375; (Marsh criteria (1) n=107; (2) n=6; (3a) n=120; (3b) n=100; (3 c) n=23). 156 OGD's were performed to investigate gluten-free compliance, costing £58 500. Sedation for all procedures accounted to £729.92. Conclusion: Over 12 years, the 1317 patients underwent 1227 endoscopic procedures (700 upper GI, 527 lower GI) and cost the CCG £5 09 588. The hospital would have reimbursed (relating to latest tariff figures) £5 70 874 from the CCG. Whilst it is clear that not all the endoscopies were directly related to coeliac disease (for example, 52 lower GI procedures were part of the Bowel Cancer Screening Programme), there is still a strong demand placed on the endoscopy unit from this cohort of patients. This burden is only likely to increase, given the suspicion that ½ million people in the UK remaining undiagnosed.